Stabilization of BMIz Score is Associated with a Decrease in Visceral Fat in Children with Obesity - Naik, Yashoda; Allen, David B.; Eickhoff, Jens; Carrel, Aaron L. (Hormone and Metabolic Research, 2020)
BMIz-score (BMIz) is commonly used to assess childhood obesity. Whether change in BMIz score predicts change in visceral fat remains unclear. The objective of the work was to study changes in visceral fat, cardiovascular fitness (CVF), and metabolic health over 6 months in children with stable/decreased-BMIz vs. increased-BMIz. Ninety children with obesity, referred for lifestyle intervention were studied (mean age 11±3.1 years, 50% girls, 22% Hispanic). Assessment included abdominal and total fat by dual X-ray absorptiometry (DXA), sub-maximal VO2 for CVF, anthropometrics, and fasting insulin, glucose, HDL-C, triglycerides, AST and ALT at 0 and 6 months. Sixty-three children (70%) showed a stable/decrease in BMIz over 6 months. There was no significant change in total body fat between groups (−1.3±2.9% in BMIz-stable/down vs. − 0.6 ± 2.6% BMIz-up, p=0.459); however, BMIz-stable/down group showed a decrease in visceral fat compared to the BMIz-up group (−258±650 g vs.+137±528 g, p=0.009). BMIz-stable/down group also demonstrated increased CVF (+1.2 ml/kg/min, p<0.001), not seen in the BMIz-up group. Neither group had significant changes in metabolic markers. Preventing BMIz increase in obese children predicts a significant decrease in visceral fat even if total body fat is unchanged. This is often associated with increased fitness. Thus, increasing fitness level and keeping BMI stable are strategic initial goals for obese children.
Keywords: BMI; child; visceral fat; VO2 max